THE ASSESSMENT OF NURSES’ KNOWLEDGE AND ATTITUDE TOWARDS INFECTION CONTROL PRACTICES IN TERTIARY CARE HOSPITAL OF LAHORE, PAKISTAN - ANAYAT , A; HAMEED , NA; RASHEED , R; JABEEN , S; NAWAZ , B (Biological and Clinical Sciences Research Journal, 2024)
Infection control is a critical aspect of hospital safety, ensuring the well-being of both patients and healthcare providers. Nurses play a central role in executing infection control measures; thus, their knowledge and attitudes towards these procedures are vital for effective healthcare delivery. Objective: The aim of this study is to evaluate nurses' understanding of and attitudes toward infection control procedures within a hospital setting. Methods: This cross-sectional descriptive study was conducted in a selected hospital where data was collected from 150 nurses using a structured questionnaire after obtaining participant consent. A convenient sampling method was employed to meet inclusion criteria. The analysis focused on the levels of knowledge and attitudes toward infection control, assessed through validated survey tools. Results: Among the nurses surveyed, 47.3% demonstrated a high level of knowledge regarding infection control, 22.0% scored well, and 30.7% showed poor knowledge. In terms of attitudes, 94.7% of participants displayed positive attitudes towards infection control measures, whereas 5.3% exhibited negative attitudes. Conclusion: The study revealed that while a significant portion of nurses possess substantial knowledge regarding infection control, there is a notable percentage that requires further education to enhance their understanding. The overall positive attitude towards infection control suggests a strong foundation for implementing effective practices but highlights the need for continuous professional development to address knowledge gaps.